The Influence of Hijab Trends, Product Reviews, and Product Ratings on Hijab Purchase Decisions by Shopee Users in Pontianak - Faaiza Soraya Khalida; Heni Safitri; Mahardika Agung Madepo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of Hijab Trends, Product Reviews, and Product Ratings on Hijab Purchase Decisions by Shopee users in Pontianak City. This research uses a quantitative approach with a causal associative research design. The sampling technique used was purposive sampling with a total of 203 Shopee users in Pontianak City who had purchased hijab products. Primary data were collected through the distribution of online questionnaires using a five-point Likert scale and were then analyzed using multiple linear regression after passing validity tests, reliability tests, and classical assumption tests. The results of the analysis show that partially, Hijab Trends, Product Reviews, and Product Ratings have a positive and significant effect on Hijab Purchase Decisions. Simultaneously, Hijab Trends, Product Reviews, and Product Ratings also have a significant effect on Hijab Purchase Decisions. The correlation coefficient (R) value of 0.863 indicates a strong relationship between the independent variables and the dependent variable, while the coefficient of determination (R2) value of 0.744 indicates that 74.4% of the variation in Hijab Purchase Decisions can be explained by Hijab Trends, Product Reviews, and Product Ratings, while the remaining percentage is influenced by other factors outside the research model. The findings of this study indicate that Hijab Purchase Decisions by Shopee users in Pontianak City are influenced by the relationship between Hijab Trends, Product Reviews, and Product Ratings.